Study of Macroalgae Biodiversity in the western Algerian Coast, Tenes - BELHAOUARI BENKHEDDA, TRAICHE ABDERRAOUF,; OMAR, ROUEN-HACEN (Current Botany, 2018)
During this study we evaluated the spatio-temporal distribution of macroalgae in the western Algerian coast. This work was carried out in the intertidal zone near the municipality of Tenes. We carried out a seasonal sampling from July 2016 to April 2017, at four different sites. Nine species were identified. The highest species richness was observed in summer and early autumn. The most abundant algae observed were Ulva et Cystoseira. Ulva alga achieved the highest recovery rate 60,33% in Spring. Laurencia obtusa and Spongomorpha arcta were the least abundant. Algae of economic interest have been observed in the coast of Tenes.